The New Principles of Management - Kozminski, Andrzej; Jemielniak, Dariusz (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2013)
The New Principles of Management is a textbook meant for European students of principles of management. Developed basing mainly on international cases as well as drawing from international examples of managerial practices, it attempts to address the needs of globalized companies better than other, typically US-centric textbooks. The New Principles of Management challenges many of the fossilized and outdated management notions and covers the topics most relevant for modern 21st century organizations, rather than their historic developments.
Keywords: management; Evropa střední a východní; Europe, Central and Eastern; elektronické knihy; electronic books